Concentration, market imperfections, and interbranch organization in the Italian processed tomato supply chain - Lukáš Čechura; Antonella Samoggia; Tinoush Jamali Jaghdani (Agricultural Economics, 2024)
The increase in market concentration and market power in the food supply chain is an issue of concern globally. This study focuses on an analysis of market imperfections in the Italian processed tomato food supply chain by considering changes in its supply chain governance from 2006–2018. The identification of the degree of non-competitive behavior is based on the derived mark-down and mark-up models using the latest developments in stochastic frontier methodology. The estimated models reveal some degree of non-competitive behavior in the input as well as in the output processing market. However, in consideration of the results on the supply chain governance during the study period, we argue that the establishment of an Interbranch Organization (IBO) could create fairly stable long-term food supply chain relationships benefitting all IBO members and in particular farmers despite the significant change in concentration levels in the Italian tomato processing sector after 2015.
Keywords: D43; D71; L11; L13; Q13; 330; concentration rate; food chain; interbranch organizations; Italy; market imperfections; stochastic frontier analysis; tomatoes